2016
DOI: 10.18632/oncotarget.13167
|View full text |Cite
|
Sign up to set email alerts
|

SNHG8 is identified as a key regulator of epstein-barr virus(EBV)-associated gastric cancer by an integrative analysis of lncRNA and mRNA expression

Abstract: The Epstein–Barr virus (EBV) is associated with a variety of cancers, including gastric cancer, which has one of the highest mortality rates of all human cancers. Long non-coding RNAs (lncRNAs) have been suggested to have important causal roles in gastric cancer. However, the interaction between lncRNAs and EBV has not yet been studied. To this end, we sequenced 11,311 lncRNAs and 144,826 protein-coding transcripts from four types of tissue: one non-EBV-infected gastric carcinoma (EBVnGC) and its adjacent norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 89 publications
(99 reference statements)
1
43
0
Order By: Relevance
“…Previous research indicated that lncRNA SNHG8 is highly expressed in EBV-associated GC [19]. To elucidate the expression levels of SNHG8 in HCC tissues, we found that SNHG8 expression was noticeably increased in HCC tissues (n = 23) as compared with the adjacent normal tissues (n = 23; Fig.…”
Section: Lncrna Snhg8 Expression Was Upregulated In Human Hcc Tissuesmentioning
confidence: 75%
“…Previous research indicated that lncRNA SNHG8 is highly expressed in EBV-associated GC [19]. To elucidate the expression levels of SNHG8 in HCC tissues, we found that SNHG8 expression was noticeably increased in HCC tissues (n = 23) as compared with the adjacent normal tissues (n = 23; Fig.…”
Section: Lncrna Snhg8 Expression Was Upregulated In Human Hcc Tissuesmentioning
confidence: 75%
“…Small microRNAs (miRNAs) and long noncoding RNAs (IncRNAs) play important post-transcriptional gene regulatory roles in EBVaGC [39, 40]. EBV was the first virus in which miRNAs were discovered [40].…”
Section: Pathophysiology and Tumorigenesismentioning
confidence: 99%
“…IncRNAs are associated with larger tumors, greater invasion and reduced survival rates in gastric cancer [39]. Huang et al showed increased expression of an IncRNA, known as SNHG8 in EBVaGC [39].…”
Section: Pathophysiology and Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNAs (lncRNAs) are over 200 nucleotides in length, lack protein‐coding ability, and retain essential functions in a range of biological processes and collected evidence has confirmed the impact of lncRNAs on cancer initiation, development, and progression . For example, the lncRNA SNHG8 was found to affect several GC‐specific pathways and target genes of EBV . SNHG8 expression was reported to be upregulated 14 fold in GC compared with normal gastric tissues, and in particular, it can increase to still higher levels in EBVaGC than in EBV‐negative GC .…”
Section: Introductionmentioning
confidence: 99%